Kontribusi Pendapatan Usahatani Padi Sawah Tadah Hujan Terhadap Pendapatan Keluarga (Studi Kasus di Lingkungan Talamangape Kelurahan Allepolea Kecamatan Lau Kabupaten Maros) - Rahmatia Baso; Mohammad Anwar Sadat; Arifin Arifin (Universitas Muslim Maros, 2022)
The purpose of this study was to find out how much the contribution of rainfed paddy rice farming to family income in the Talamangape Neighborhood of Allepolea Village, Lau District, Maros Regency. This research was carried out in March to June 2022. he population of this study was all farmers (125 farmers) who tried to get rice in rainfed fields at the study location. The sample in this study was taken by 25 from 20% of farmers. Farmer samples were taken using the Random Sampling method. The analysis used in this study is income analysis. The results showed that the average income received by farmers where for paddy rice farming income was Rp. 171,875,000, and income from non-agricultural farming was Rp. 44,550,000 so that it could make a sufficient contribution to the income of rainfed paddy rice farming business to the income of farmer families by 79.41%.